Satisfying Reason - Rescher, N. author. aut Link
XII, 246 p.
Keywords: Leibniz said with a mixture of admiration and inspiration that the Duchess Sophie of Hannover always wanted to know the reason why behind the reason why. And that is just how rationality works: it wants to leave no loose ends to understanding, seeking to enable us to understand things through to the bitter end. In the twelve chapters that make up Satisfying Reason, Rescher develops and defends the following perspective: That rationality is a cardinal virtue in cognitive matters. That this is not something simple and cut-and-dried: in the pursuit of truth through the development of knowledge we face obstacles -- sometimes even insuperable ones. All that we can do is the best we can, realizing that even our very best may still be imperfect. Nevertheless, the venture is far from hopeless. While absolutes are unattainable in the cognitive venture, some solutions are situationally optimal, being comparatively the best that can be managed under the circumstances. That reason itself enables us to come to terms with this state of affairs, urging us to accept the best we can do as good enough. Satisfying Reason is an explanation of the presuppositions and methods of rational enquiry, an original exercise in metaknowledge, developing a systematic body of knowledge about the scope and limits of knowledge itself.